2017
DOI: 10.1111/lam.12770
|View full text |Cite
|
Sign up to set email alerts
|

Deleting the first disulphide bond in an arenicin derivative enhances its expression in Pichia pastoris

Abstract: Disulphide bond formation is an important step in the protein expression and can also influence protein secretion. A deletion of the first disulphide bond in NZ17074 increased the secreted level of target protein, and its antimicrobial activity was almost unaffected by the deletion of the first disulphide bond. The first disulphide bond in NZ17074 is favourable for correctly forming another disulphide bond during expression but not necessary for its activity. This may help design and produce a novel class of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Although this precludes their development as candidate antimicrobials, artificial modified analogs were designed based on their structure, in order to decrease their adverse effects and to enhance the antimicrobial properties. Novel derivatives named NZ17074, N2, and N6 were designed and synthesized as linear or with more disulfide bonds by amino acid substitution [90,97,106,107]. By showing a higher antimicrobial activity and a lower cytotoxicity, these latter derivatives were more powerful than the parent molecule.…”
Section: Amps Diversity In Annelids and Nematodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this precludes their development as candidate antimicrobials, artificial modified analogs were designed based on their structure, in order to decrease their adverse effects and to enhance the antimicrobial properties. Novel derivatives named NZ17074, N2, and N6 were designed and synthesized as linear or with more disulfide bonds by amino acid substitution [90,97,106,107]. By showing a higher antimicrobial activity and a lower cytotoxicity, these latter derivatives were more powerful than the parent molecule.…”
Section: Amps Diversity In Annelids and Nematodesmentioning
confidence: 99%
“…By showing a higher antimicrobial activity and a lower cytotoxicity, these latter derivatives were more powerful than the parent molecule. Therefore, these positive results suggest these AMPs as potential candidates for antibacterial drug development [81,107,108].…”
Section: Amps Diversity In Annelids and Nematodesmentioning
confidence: 99%
“…A series of arenicin-3 analogs, such as NZ17074, N2 and N6, were also designed and synthesized to improve antibacterial activity [ 35 , 36 , 37 ]. NZ17074, N2 and N6 displayed more potent antibacterial activity against Escherichia , Salmonella , Pseudomonas , Staphylococcus and Listeria , except Bacillus and Candida , than their parents and had a high capacity to bind to LPS by molecular docking and BODIPY’-TR-cadaverine (BC) displacement assays.…”
Section: Antibacterial/antiendotoxic Peptides or Proteins From Varmentioning
confidence: 99%
“…The first disulfide bond in the arenicin-3 derivative-NZ17074 was deleted, fused with a SUMO partner and expressed in P. pastoris . The result showed that the production level of N6 was increased by 1.4-fold compared to NZ17074, indicating the reduced toxicity to host cells after removing the first disulfide bond and fusing with SUMO [ 37 ]. Hydrophobicity of LPS-neutralizing antibacterial peptides, such as arenicin-1 or proteins, is closely related to cytotoxicity.…”
Section: Challenges and Strategies For Antibacterial And Antiendotmentioning
confidence: 99%
See 1 more Smart Citation